2012
DOI: 10.1111/j.1745-7599.2012.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Caring for military spouses in primary care

Abstract: Healthcare providers should routinely inquire about a patient's possible military affiliation. Military spouses need to be assessed for current stress levels and coping behaviors used in order to provide the most appropriate recommendations and referrals. As healthcare providers, understanding the unique demands of the military lifestyle is necessary to provide effective quality care with optimal health outcomes in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Despite the employment difficulties spouses encountered, overcoming the challenges of finding employment was described by some spouses as having boosted their self-esteem and provided an opportunity for establishing social connections following an accompanied posting. Studies have suggested that good quality and supportive relationships can be difficult for military spouses to build and maintain because of frequent moves (Finch, 1983; Jervis, 2011; Orthner and Rose, 2009; Padden and Posey, 2013) and that spouses who are unable to build connections within the military community may be at greater risk of social isolation, stress, psychological distress and mental health problems (Cohen and Wills, 1985; Dalgard et al, 1995; Greenblatt et al, 1982; Knickmeyer et al, 2002; Maulik et al, 2010; Olstad et al, 2001; Padden and Posey, 2013; Paykel, 1994). Findings from this study suggest that spouses who are able to work may be better able to mitigate the disruptive social impact of accompanied postings through the development of new networks, potentially improving mental health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the employment difficulties spouses encountered, overcoming the challenges of finding employment was described by some spouses as having boosted their self-esteem and provided an opportunity for establishing social connections following an accompanied posting. Studies have suggested that good quality and supportive relationships can be difficult for military spouses to build and maintain because of frequent moves (Finch, 1983; Jervis, 2011; Orthner and Rose, 2009; Padden and Posey, 2013) and that spouses who are unable to build connections within the military community may be at greater risk of social isolation, stress, psychological distress and mental health problems (Cohen and Wills, 1985; Dalgard et al, 1995; Greenblatt et al, 1982; Knickmeyer et al, 2002; Maulik et al, 2010; Olstad et al, 2001; Padden and Posey, 2013; Paykel, 1994). Findings from this study suggest that spouses who are able to work may be better able to mitigate the disruptive social impact of accompanied postings through the development of new networks, potentially improving mental health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 20 years, researchers have shown a great deal of interest in the experience and coping of military families after their soldier sons deploy to war zones, with a focus on soldiers’ spouses and/or children (Crow and Myers-Bowman, 2011). Family members have been found to report fear of loss and anticipatory anxiety, which can in turn lead to symptoms of distress, depression, anxiety, and reduced well-being among spouses (e.g., Rosen and Durand, 2000; Padden and Posey, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Military partners are the “hidden heroes” (FoxNews.com, ) in the holistic care of veterans struggling with PTSD symptoms. They live in a multicultural environment steeped in military tradition, social isolation, and a recurrent reformation of social networks (Padden & Posey, ). These partners manage geographical relocations and resettling to an unfamiliar locale, all while attempting to sustain positive family dynamics.…”
Section: Military Partners: Critical To Holistic Ptsd Carementioning
confidence: 99%